TEACHERPRENEUR SEBAGAI WUJUD INOVASI PENDIDIKAN BERBASIS KEWIRAUSAHAAN - Baehaqi, Sirojul; Baedhowi, Kholil; Kurniati, Edy Dwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study explores the concept of entrepreneurship from various theoretical, historical, and practical perspectives, particularly in the context of education. The discussion begins with the history of entrepreneurship from prehistoric times, the agricultural revolution, the Middle Ages, the industrial revolution, to the modern digital era marked by technological transformation and globalization. Specifically, this paper highlights the concept of the teacherpreneur, which integrates the roles of teacher and entrepreneur capable of creating innovation in the field of education. As teacherpreneurs, teachers are expected not only to teach but also to become agents of change through the development of ethical and sustainable education-based enterprises. This research uses a qualitative method with a literature review approach. The research stages involve collecting data and information from various relevant written sources, such as books, scientific journals, articles, and credible digital literature discussing entrepreneurial concepts. The findings show that a deep understanding of entrepreneurial concepts and theories is crucial to be applied in education to create an adaptive, innovative, and highly competitive system. The concept of entrepreneurship encompasses a broad understanding, from definitions and historical developments to interdisciplinary theories that explain the vital role of entrepreneurs in creating value, innovation, and economic growth. In the modern era, this concept has evolved into the educational domain through the idea of the teacherpreneur, a teacher who acts as both an educator and an innovator in the educational landscape. ABSTRAK Penelitian ini membahas mengenai konsep wirausaha dari berbagai perspektif teoritis, historis, dan aplikatif, khususnya dalam konteks pendidikan. Pembahasan dimulai dari sejarah kewirausahaan sejak masa prasejarah, revolusi pertanian, abad pertengahan, revolusi industri, hingga era digital modern yang ditandai dengan transformasi teknologi dan globalisasi. Secara khusus, makalah ini mengangkat konsep teacherpreneur, yaitu integrasi peran guru sebagai pendidik dan wirausahawan yang mampu menciptakan inovasi dalam dunia pendidikan. Guru sebagai teacherpreneur diharapkan tidak hanya mengajar, tetapi juga menjadi agen perubahan melalui pengembangan bisnis berbasis pendidikan yang etis dan berkelanjutan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur. Tahapan penelitian dilakukan dengan mengumpulkan data dan informasi dari berbagai sumber tertulis yang relevan, seperti buku, jurnal ilmiah, artikel, dan literatur digital terpercaya yang membahas konsep kewirausahaan. Hasil kajian menunjukkan bahwa pemahaman mendalam tentang konsep dan teori kewirausahaan sangat penting untuk diterapkan dalam dunia pendidikan guna menciptakan sistem yang adaptif, inovatif, dan berdaya saing tinggi. Konsep kewirausahaan mencakup pemahaman yang luas, mulai dari definisi, sejarah, hingga teori-teori lintas disiplin yang menjelaskan peran penting wirausaha dalam menciptakan nilai, inovasi, dan pertumbuhan ekonomi. Di era modern, konsep ini berkembang ke ranah pendidikan melalui gagasan teacherpreneur, yaitu guru yang berperan sebagai pendidik sekaligus inovator dalam dunia pendidikan.